The Effectiveness of Cognitive Remediation Programs among Children with Neuro-Developmental Disorder (Dyslexia) - Khuntia, Sipra; Priyadarshini Das, Prangya Paramita; Behera, Naresh (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Background: Recent studies highlight that children with reading and learning disabilities experience greater difficulties in cognitive processes than normal children. Meanwhile, previous research provides evidence that psychological interventions can enhance reading and learning skills. However, the application of cognitive interventions for this population is still lacking. Objective: The study attempted to improve reading skills in dyslexic children by using cognitive remediation programs and to explore the efficacy of Cognition Enhancement Training (COGENT) and PASS Reading Enhancement Program (PREP). Methods: One group pre-test and post-test research design has been used in this study. Initially, 147 children in class V of 10-11 years were purposively selected from three schools in the Cuttack district of Odisha. In the screening process, the Test of Word Reading Efficiency (TOWRE) test was applied among children, and 14 children were identified as dyslexic. The Word Reading Mastery Test-Revised (WRMT-R) was used to evaluate the effectiveness of intervention programs. A correlated sample t-test was used to examine the significant increase in scores after interventions. Results: The t-test value for word identification was 13.88 (p <0.01), and for passage comprehension was 14.38 (p <0.01) of WRMT-R. The intervention of COGENT & PREP significantly enhanced reading skills such as phonetic decoding efficiency, phonological awareness, phonological memory, rapid naming, reading mastery, and planning ability after receiving these programs. Conclusion: The COGENT and PREP remediation programs have been statistically proven to enhance the reading skills of dyslexic children.